Factors Affecting Employee Retention through Perceived Organizational Support (Survey of Auditor Employees at the BPKP Office) - Sumardi Sumardi; Hapzi Ali; Agung Dharmawan Buchdadi (Journal of Accounting and Finance Management, 2021)
Factors that influence employee retention through perceived organizational support is an article to prove whether perceived organizational support is proven to mediate Career Development Practices, Employee Retention, Organizational Justice on employee retention. This research approach uses the SEM-PLS data analysis method. The findings of this study are: 1) Career Development has a positive effect on Employee Retention through Perceived Organizational Support; 2) Organizational Justice has a positive effect on Employee Retention through Perceived Organizational Support; 3) Trust in Organization has a positive effect on Employee Retention through Perceived Organizational Support.